2016
DOI: 10.1007/s00330-016-4444-x
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast detectability and spatial resolution with model-based Iterative reconstructions of MDCT images: a phantom and cadaveric study

Abstract: • Model- based Iterative Reconstruction improves detectability of low contrast object. • With model- based Iterative Reconstruction, spatial resolution is dose and contrast dependent. • Model-based Iterative Reconstruction algorithms enable improved IQ combined with dose-reduction possibilities. • Improvement of SR and LC detectability on the same IMR data set would reduce reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Its value for organ recognition (segmentation), lesion detection, and lesion characterization has been explored (11) and its ability to detect and reduce the image noise has been demonstrated (12À16). Unlike the conventional noise reduction methods, which involve a trade-off between spatial resolution and noise reduction (6,17), deep learning lowers the image noise and increases spatial resolution simultaneously (9). In this phantom study we examined the noise characteristics, spatial resolution, and task-based detectability of DLR images.…”
Section: Introductionmentioning
confidence: 99%
“…Its value for organ recognition (segmentation), lesion detection, and lesion characterization has been explored (11) and its ability to detect and reduce the image noise has been demonstrated (12À16). Unlike the conventional noise reduction methods, which involve a trade-off between spatial resolution and noise reduction (6,17), deep learning lowers the image noise and increases spatial resolution simultaneously (9). In this phantom study we examined the noise characteristics, spatial resolution, and task-based detectability of DLR images.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers have reported that peak shifts, like that present in the ADMIRE NPS, did not influence to diagnostic performance and instead improved low-contrast detectability. 4 As IIR mostly maintains the spatial resolution of FBP and reduces the NPS over the entire frequency range, its SP is uniformly better than that of FBP, thus resembling the properties achieved by dose increase. As the SP 2 at 2.5, 5, and 10 mGy with IIR were comparable to those at 5, 10, and 20 mGy with FBP, respectively, the dose reduction with IIR was estimated at approximately 50%.…”
Section: Discussionmentioning
confidence: 90%
“…F I G . However, some researchers have reported that peak shifts, like that present in the ADMIRE NPS, did not influence to diagnostic performance and instead improved low-contrast detectability 4. Images processed with (left column) FBP and (middle column) IIR, and corresponding subtraction images (right column), for the rod object for the TTF measurement, a bar-pattern phantom, and a clinical abdomen image.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scatter radiation is normally corrected by mathematical algorithms [50, 51], which may not equally correct for scatter induced artifacts in every situation. On the other hand, iterative reconstruction algorithms of the MDCT decrease image noise and alter the image impression [52, 53], which was not available or applied in CBCT. Due to the reasons given above, a direct comparison between different CBCT devices or CBCT and MDCT machines is further complicated regarding objective, and especially subjective image quality.…”
Section: Discussionmentioning
confidence: 99%